Diagnostics and prevention of suicidal behavior among teenagers - А. V. Li; D. E. Kadyrzhan; V. V. Kozlov; O. Kh. Aimaganbetova; А. K. Fayzullina (Хабаршы. Психология және социология сериясы, 2020)
Abstract. This article is devoted to an empirical study of suicidal behavior among adolescents, as well as the process of creating an author’s training. Throughout conducting of the research, we proceeded from the fact that today the issue under study is very relevant. The object of our study was adolescents of educational institutions, and the subject of their suicidal behavior. We conducted a battery of methods consisting of 4 methods: the G. Eisenck questionnaire, the “Incomplete offers” method, the Albert Ellis test, and the method of studying the locus of control of J. Rotter. The study revealed that mainly modern adolescents have high personal anxiety, as well as the negative perception of the people around them, as a result of which, mostly adolescents find neither support nor help from people close to them. Most adolescents showed high rates on the scales of “Catastrophization”, “Commitment in relation to oneself”. The locus of control is mostly external to them, which indicates that adolescents tend to attribute their failures to external factors. Based on the results obtained, training was proposed that will contribute to the correction of these factors, as a result of which it will help in the prevention of suicidal behavior among adolescents. Key words: suicidal behavior, adolescents, external and internal factors, author’s training.